Skills-Based Grading: a novel approach to teaching formal semantics - O'Leary, M; Stockwell, R (Linguistics Society of America, 2021)
This paper reports an implementation of ‘Skills-Based Grading’ (SBG) in a formal semantics course. In traditional grading, every part of every assignment contributes to the final grade. Students are required to progress along a uniform timeline, with partial credit as a safety net. In SBG, by contrast, the course is composed of skills. Students are given multiple opportunities to demonstrate mastery in each skill, but full proficiency is required to gain credit. Zuraw et al. (2019) pioneered the use of SBG in linguistics for phonetics and phonology. SBG is known to work well for skills that require algorithmic approaches to arrive at inarguably correct answers. In applying SBG to semantics, we show that it is just as effective for more abstract and philosophical skills. Based on survey and grade data, we substantiate claims that SBG improves student learning, encourages more effective study, lowers student stress, and achieves more equitable outcomes. Since this paper reports our first use of SBG, we conclude with some reflections on improvements for the future.